Kelimpahan Makrozoobenthos di Situ Cijeruk Kabupaten Sukabumi - Iqbal Julian Pasca Nisara; Novita Mz; Arif Supendi; Pelita Octorina (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2024)
This study aims to identify the abundance of macrozoobenthos in Situ Cijeruk, Sukabumi Regency, West Java. Sampling was conducted at five stations with different environmental characteristics: Station 1 (Inlet), Station 2 (Succession Waters), Station 3 (Area with Human Activities), Station 4 (Outlet), and Station 5 (Industrially Polluted Waters). The purposive sampling method was used in this study, with sediment collected using an Eckman grab. The results identified five species of macrozoobenthos: Brotia testudinaria, Thiara scabra, Penaeus merguiensis (De Man), Radix rubiginosa, and Tylomelania. The highest abundance was found at Station 2 with 50 individuals/m², while the lowest was at Station 3 with 8 individuals/m².